Advances in conceptual modeling : ER 2016 Workshops, AHA, MoBiD, MORE-BI, MReBA, QMMQ, SCME, and WM2SP Gifu, Japan, November 14-17, 2016 proceedings (Switzerland : Springer, 2016)
This book constitutes the refereed proceedings of seven workshops and a symposium, held at the 35th International Conference on Conceptual Modeling, ER 2016, in Gifu, Japan. The 19 revised full and 3 keynote papers were carefully reviewed and selected out of 52 submissions to the following events: Conceptual Modeling for Ambient Assistance and Healthy Ageing, AHA 2016; Modeling and Management of Big Data, MoBiD 2016; Modeling and Reasoning for Business Intelligence, MORE-BI 2016; Conceptual Modeling in Requirements and Business Analysis, MREBA 2016; Quality of Models and Models of Quality, QMMQ 2016; and the Symposium on Conceptual Modeling Education, SCME 2016; and Models and Modeling on Security and Privacy, WM2SP 2016.
También disponible en formato EPUB